A Tisza István-Tudományegyetem karainak beszámoló jelentései az 1944/45. tanévről - Mudrák, József (Gerundium, 2011)
The Report s of the Faculties of the Academic Year of 1944–1945. Indubitably, the most difficult period in the history of the University of Debrecen was the last year of World War Two. The relatively undisturbed operation of the institution before the autumn of 1944 soon became impossible to maintain. The approaching battle-front and the subsequent entry of the Soviet troops resulted in the departure of a large segment of the professorial faculty. Those who stayed behind tried to maintain a semblance of order through emergency measures.Wartime damage, the utilization of the building facilities for other purposes, and teacher shortage posed almost impossible problems to those who felt responsible for making the university function. The documents that are made available here—the reports of the faculties prepared in the spring of 1945—make it clear what a superhuman struggle was carried on to maintain the operation of the university for almost a year.